2017
DOI: 10.1177/1747954117725286
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership and organizational citizenship behavior: Mediating role of affective commitment

Abstract: The purpose of this study was to examine the relationships between transformational leadership style, affective commitment, and organizational citizenship behavior in the athletic director-coach relationship. This study particularly focused on the mediating effect of affective commitment on the relationship between transformational leadership and organizational citizenship behavior. Athletic head coaches in NCAA Division II programs (n ¼ 244) completed the questionnaires measuring perceptions of the transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(99 citation statements)
references
References 54 publications
(103 reference statements)
8
55
0
6
Order By: Relevance
“…These outcomes are consistent with prior empirical research (e.g. Jha, 2014;Khalili, 2017;Lee, Woo, & Kim, 2018;Mekpor & Dartey-Baah, 2017;Suliman & Al-Obaidli, 2013). For example, in a study of 50 organizations in Iran, with a sample of 2,021 employees, Khalili (2017) studied the influence of transformational leadership on ocb.…”
Section: Final Considerationssupporting
confidence: 84%
“…These outcomes are consistent with prior empirical research (e.g. Jha, 2014;Khalili, 2017;Lee, Woo, & Kim, 2018;Mekpor & Dartey-Baah, 2017;Suliman & Al-Obaidli, 2013). For example, in a study of 50 organizations in Iran, with a sample of 2,021 employees, Khalili (2017) studied the influence of transformational leadership on ocb.…”
Section: Final Considerationssupporting
confidence: 84%
“…We observed the similar results of the impact of organizational commitment on citizenship behavior since the organizational commitment of employees drives them to escalate the firm values and image through taking participation in pro-organizational activities. The findings of Afsar, Shahjehan, Cheema, and Javed (2018), Lee, Woo, and Kim (2018), Uddin et al (2019), and Howladar (2017) showed the similar estimates on this proposed hypothesis.…”
Section: Discussionsupporting
confidence: 53%
“…However, not all dimensions of organizational commitment have benefits to organizational effectiveness. Prior studies have proved the positive relationship between affective commitment and organizational performance [ 59 ]. Specifically, affective commitment has a strong effect on organizational effectiveness, including the negative effect on turnover rate, absenteeism rate, and negative organizational behavior [ 60 ].…”
Section: Theory and Hypothesesmentioning
confidence: 99%